PROBLEMS OF APPLICATION OF MARKETING TECHNOLOGIES AND TOOLS IN HIGHER EDUCATION ORGANIZATIONS - R. V. Gavva; E. N. Lozhkomoeva (Вестник университета)
The article considers marketing technologies and tools used in the educational process of higher educational institutions. The paper emphasizes specifics and determines conditions of their application. The authors indicate new realities in which educational organizations find themselves and designate the need for changes in the conduct of educational activities. The study argues the expediency of using marketing technologies and tools in educational activities due to the active  development of the market of educational services. The article defines the directions of activity of the educational organization of higher education  where it is necessary to use marketing technologies and tools. The paper  highlights a number of problems related to the introduction and use of  marketing technologies and tools in the educational process of higher  educational institutions. The authors formulate conclusions on the need for  the use of marketing technologies and tools in higher education organizations.